Applications of Duyen Hai - 1 thermal power pant’s fly ash and Hoa Phat steelmaking plant’s blast furnace slag in geopolymer concrete fabrication - Minh, Le Tuan (Vietnam Journal of Science and Technology, 2022)
Currently, non-cement alkaline activated concretes, using fly ash instead of conventional cement binder, have been widely used in construction around the world. However, in Viet Nam researches on geopolymer concretes are still very limited. Meanwhile, coal-fired thermal power plants in Viet Nam annually generate about 13 million tons of fly ash, potentially causing environmental pollution. Therefore, the use of these raw materials for concrete making not only minimizes environmental pollution but also avoids wasting resources. This paper presents study results on the mechanical properties of geopolymer concrete using fly ash of the 1,245 MW Duyen hai - 1 thermal power plant and blast furnace slag of Hoa Phat steelmaking plant. The suitable ratio of liquid glass/NaOH used in this study was about 3.7. At this value, the compressive, flexural and tensile strengths of the geopolymer concrete have reached 43.2 MPa, 6.62 MPa and 87,780 N, respectively. In addition, geopolymer concrete samples were impervious and their mechanical properties were almost unchanged after soaking in various solutions for a period of 4 months. Furthermore, interlocking blocks were fabricated from this geopolymer concrete (with the same composition as sample M6), based on the TCVN 9901:2014 standard on Hydraulic structures and Requirements for sea dike design. These blocks were used to reinforce the sea dike against this year’s typhoon season in central Viet Nam. The success of this project greatly contributes to the effective application of fly ash and reducing environmental pollution.